2022
DOI: 10.21203/rs.3.rs-1445167/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MiR-17-5p/RRM2 Regulated Gemcitabine Resistance in Lung Cancer A549 Cells

Abstract: Background To investigate the roles of miR-17-5p/RRM2 in A549/G+. Methods Cell survival was analyzed by CCK8 kit and clone formation experiment; The mRNA expression level was detected by qRT-PCR, and the protein level was compared by Western blotting; And flow cytometry for cell cycle detection; The target gene of miR-17-5p was verified by double luciferase activity experiment. Results CCK8 assay displayed that miR-17-5p’s overexpression can let A549/G + cells turn into sensitive ones; in turn, in the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Another limitation of the present work is the lack of in vivo data, and animal experiments may make our conclusion more convincing. Finally, miR‐17‐5p is associated with drug resistance of NSCLC, while the expression characteristics of miR‐17‐5p in NSCLC are indeed controversial (Chatterjee et al., 2014; Ma et al., 2023; Zhang et al., 2017). In this case, the expression pattern of miR‐17‐5p in NSCLC patients, especially the patients with cisplatin resistance, should be examined in the following work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another limitation of the present work is the lack of in vivo data, and animal experiments may make our conclusion more convincing. Finally, miR‐17‐5p is associated with drug resistance of NSCLC, while the expression characteristics of miR‐17‐5p in NSCLC are indeed controversial (Chatterjee et al., 2014; Ma et al., 2023; Zhang et al., 2017). In this case, the expression pattern of miR‐17‐5p in NSCLC patients, especially the patients with cisplatin resistance, should be examined in the following work.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the miRNA 17 family targets transforming growth factor β receptor 2 in NSCLC cells, and reduces cisplatin resistance in NSCLC cells (Jiang et al., 2014). Another study reports that, miR‐17‐5p sensitize A549 cells to gemcitabine via regulating RRM2 (Ma et al., 2023). In this work, miR‐17‐5p is revealed to be markedly down‐modulated in cisplatin‐resistant NSCLC cells, and β‐elemene facilitates miR‐17‐5p expression, and miR‐17‐5p overexpression increases cisplatin sensitivity of NSCLC‐resistant cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that RRM2, an oncogene, plays a critical role in the proliferation, migration, invasion, and drug resistance of breast cancer cells, small cell lung cancer cells, renal clear cell carcinoma cells, and pancreatic cancer cells (29)(30)(31)(32). In lung adenocarcinoma, suppression of RRM2 also inhibits the proliferation, migration and invasive ability of lung adenocarcinoma cells (33)(34)(35)(36). However, there is still limited research on the specific mechanism of action of RRM2 in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the downstream mechanisms of RRM2 in lung adenocarcinoma, Ma et al (34) discovered that RRM2 may influence the sensitivity of A549 cells to gemcitabine by modulating the phosphorylated phosphatase and tensin homolog/PI3K/AKT signaling pathway. Another study demonstrated that suppression of RRM2 expression not only inhibits the malignant behavior of lung adenocarcinoma cells but also synergistically enhances the efficacy of radiotherapy in inducing cell death (35).…”
Section: Discussionmentioning
confidence: 99%